2020
DOI: 10.1093/eurheartj/ehaa758
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spironolactone on cardiovascular function and markers of fibrosis in people at increased risk of developing heart failure: the heart ‘OMics’ in AGEing (HOMAGE) randomized clinical trial

Abstract: Aims  To investigate the effects of spironolactone on fibrosis and cardiac function in people at increased risk of developing heart failure. Methods and results  Randomized, open-label, blinded-endpoint trial comparing spironolactone (50 mg/day) or control for up to 9 months in people with, or at high risk of, coronary disease and raised plasma B-type natriuretic peptides. The primary endpoint was the interaction between base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
149
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 104 publications
(160 citation statements)
references
References 44 publications
11
149
0
Order By: Relevance
“…One smaller study using EMB and circulating PICP in 25 DCM patients demonstrated that both levels of PICP and histological fibrosis decreased after treatment with spironolactone 31 . In the HOMAGE (‘Heart Omics in AGEing’) trial, 527 persons who are at risk of developing HF demonstrated similar decreasing levels of PICP after spironolactone treatment, with corresponding reductions in ventricular pre‐ and afterload 32 . Also, a prospective study of 60 CRT patients showed that lower circulating PICP levels are associated with a positive response to CRT, defined by a combination of event‐free survival, no HF hospitalization and occurrence of left ventricular reverse remodelling 33 .…”
Section: Discussionmentioning
confidence: 99%
“…One smaller study using EMB and circulating PICP in 25 DCM patients demonstrated that both levels of PICP and histological fibrosis decreased after treatment with spironolactone 31 . In the HOMAGE (‘Heart Omics in AGEing’) trial, 527 persons who are at risk of developing HF demonstrated similar decreasing levels of PICP after spironolactone treatment, with corresponding reductions in ventricular pre‐ and afterload 32 . Also, a prospective study of 60 CRT patients showed that lower circulating PICP levels are associated with a positive response to CRT, defined by a combination of event‐free survival, no HF hospitalization and occurrence of left ventricular reverse remodelling 33 .…”
Section: Discussionmentioning
confidence: 99%
“…People at increased risk of developing HF were randomly assigned to receive either spironolactone or standard care (ClinicalTrials.gov Identifier: NCT02556450). The rationale, trial design and main results have been published [ 5 , 6 ]. The study was approved by all relevant ethics committees and regulatory bodies.…”
Section: Methodsmentioning
confidence: 99%
“…The HOMAGE (Heart OMics in AGEing) trial showed that treatment with spironolactone (vs. usual care) in patients at risk of developing HF led to a decrease in collagen synthesis markers, N-terminal pro brain natriuretic peptide (NT-proBNP), reduced blood pressure and improved cardiac remodelling [ 5 , 6 ]. Small studies have suggested that spironolactone could impair endothelial function and increase glycated hemoglobin (HbA1c) in patients with DM [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, summarizing the effects of the addition of MRAs, two metaanalyses on improvements in cardiac function in patients with HFpEF and HFrEF restricted to echocardiography have highlighted improvements in diastolic function, especially, with improvements in E/e', E/A and atrial volume as the most consistent results following MRA treatment [14,15]. Further substantiating these results, a recent publication from the HOMAGE trial, investigating high-dose spironolactone in patients without HF, of whom 42% had diabetes, reported improvements in diastolic function [23]. A plausible explanation to the absence of change is given by the proportion of patients with baseline diastolic dysfunction in the current trial differs markedly from previous reports, with only an abnormal E/e' and LAi of 31% and 11%, respectively.…”
Section: Discussionmentioning
confidence: 95%